Beam parameter product optimization of densely arranged multi‐emitter tunnel junction cascaded laser. Issue 7 (29th March 2023) - Wang, Juwen; Xu, Chuanwang; Zhang, Weiqiao; Qu, Hongwei; Zhou, Xuyan; Qi, Aiyi; Zheng, Wanhua
Abstract: A tunnel junction cascaded semiconductor laser with thin waveguide and narrowed spacing between adjacent emitters is designed in this work. It can be concluded theoretically that the spatial size of the spots arrangement in fast axis has a greater impact on the vertical beam parameter product (BPP) of the multi‐emitter cascaded laser than the divergence angle. The measured vertical BPP of the designed narrow emitter spacing (NES) laser has been reduced 42.5%, which implies that the beam quality performance of the laser has been improved and proves the feasibility of this method. Meanwhile, the slope efficiency of the thin waveguide NES laser can reach up to 3.55 W/A under 10 ns duration pulse current. Abstract : We designed a triple‐emitter laser with ultra‐thin emitter waveguide thickness and units spacing, as narrow as 750 nm and 1.62 µm, respectively. The better BPP is reduced 42.5% compared with the reference laser through the design.It is quite effective for directly reducing the combined beam BPPs of lasers with multiple emitters cascaded by tunnel junctions.